O sofrimento psíquico do discente universitário: uma análise crítica - Santos, Bárbara Naves dos (2021)
We sought to investigate the relationship between the university environment in undergraduate students and the expression or aggravation of psychological distress. For that, the objective of this dissertation was to carry out an analysis of the student's suffering through the understanding of the university and culture. The specific objectives were: to contextualize the university institution, highlighting the emergence of the organizational logic within it; specific points of suffering related to a particular suffering that highlights the capitalist society; analyze the suffering of undergraduate university students from the scientific discourse. The methodology used was a theoretical-conceptual research systematized from 2015 to 2019 in the SciELO database and in CAPES journals. The theoretical basis for analysis is the Critical Theory of Society or the Frankfurt School, allowing a contextualized understanding of suffering and the scientific discourse produced so far on the subject. As a result, several factors that are related to suffering stand out: personal, relational, environmental, institutional and cultural. Thus, the understanding of the university and culture enables a better understanding of student suffering, which is shaped and manifested as social suffering. Capitalism forms subjectivities, inculcates discourses that legitimize domination and violence; the denaturalization of these discourses is part of the resistance to this sickening logic. In addition, this work also permeates the understanding of the concrete conditions of the university, such as the need for investment of resources and the attack on it at its core, submitting it to the logic of the market. It is concluded that factors such as violence, bullying, gender issues and social inequalities also arise as aspects that aggravate suffering in the university context and are related to social and cultural factors that point to a repeated violence in society.